2011
DOI: 10.2174/157341111794814995
|View full text |Cite
|
Sign up to set email alerts
|

Ag+-selective poly(vinyl chloride) Membrane Electrode Based on [N,N- ethylenebis-(3-methoxy salicylaldimine)]

Abstract: A solid state silver selective poly (vinyl chloride) (PVC) membrane electrode was developed by using recently synthesized [N, N-ethylenebis-(3-methoxy salicylaldimine)] as an active component of the membrane. The best sensitivity and selectivity for Ag+ ions were obtained for the electrode membrane containing ionophore-NPOE-PVC and KTpClTB in composition of 4:62:33:1 (w/w). The proposed electrode had a Nernstian response (56.0 mV/decade) to Ag+ within the concentration range 1.0 ×10-6 to 1.0×x10-1 mol L-1and w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Organic electronics is a field that has attracted increasing attention due to their practical applications as light emitting diodes, , solar cells, transistors, super capacitors, sensors and actuators, photoswitching, , etc. Many materials can be used as organic semiconductors, including coordination compounds, polymers, hybrids, and nanocomposites. Aromatic molecules with extended π frameworks are particularly interesting for this aim .…”
Section: Introductionmentioning
confidence: 99%
“…Organic electronics is a field that has attracted increasing attention due to their practical applications as light emitting diodes, , solar cells, transistors, super capacitors, sensors and actuators, photoswitching, , etc. Many materials can be used as organic semiconductors, including coordination compounds, polymers, hybrids, and nanocomposites. Aromatic molecules with extended π frameworks are particularly interesting for this aim .…”
Section: Introductionmentioning
confidence: 99%
“…The array of potential measurements was chosen such that the higher I‾ concentration from the lower I‾ concentration. The results in Figure 4 demonstrated that the developed sensor reached its final potential very quickly and the average response time of the sensor was measured as 5 seconds in all concentration range [29,30]. 1.0×10 -2 and D: 1.0×10 -1 molL -1 I‾).…”
Section: Response Timementioning
confidence: 92%